The Existence of Career Guidance and Counseling In The Era Of The Fourth Industrial Revolution 4.0 - Putri Angelina Ginting; Taufiq, Agus; Supriatna, Mamat (Universitas PGRI Yogyakarta, 2025)
This article examines the existence of career guidance and counseling in the era of the Fourth Industrial Revolution. The significant growth of science and technology has made guidance and counseling an integral component of education. Using the method of critical appraisal and literature review, this study explores career guidance and counseling in the era of the Fourth Industrial Revolution. The results show that the existence of career guidance and counseling in the Fourth Industrial Revolution has significant implications for the increasing need for career guidance and counseling services, utilizing electronic information and communication technology devices, such as career e-counseling and career coaching. It can be concluded that individuals who participate in career guidance and counseling will be better prepared to face challenges and navigate their careers adaptively in response to future career changes. Keywords: career guidance and counseling, the era of the industrial revolution 4.0, adolescent